2010
DOI: 10.1007/s11145-010-9284-5
|View full text |Cite
|
Sign up to set email alerts
|

Basic auditory processing and developmental dyslexia in Chinese

Abstract: The present study explores the relationship between basic auditory processing of sound rise time, frequency, duration and intensity, phonological skills (onset-rime and tone awareness, sound blending, RAN, and phonological memory) and reading disability in Chinese. A series of psychometric, literacy, phonological, auditory, and character processing tasks were given to 73 native speakers of Mandarin with an average age of 9.7 years. Twenty-six children had developmental dyslexia, 29 were chronological age-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 68 publications
0
15
1
Order By: Relevance
“…The children with dyslexia did not show a significantly linear CA trajectory on this task making statistical analysis inappropriate, however a similar amount of delay was evident in the trajectory analysis. The 1 rise task has been the most consistent auditory measure differentiating children with dyslexia and controls in our studies of dyslexia in other languages (Finnish, Hämäläinen et al, 2009 ; Spanish, Goswami et al, 2011 ; Chinese, Wang, Huss, Hämäläinen, & Goswami, 2012 ). A similar 1 rise task based on complex noise rather than a sine wave was also a successful discriminator in a study of dyslexia in Dutch by Poelmans et al, (2011) .…”
Section: Discussionmentioning
confidence: 77%
“…The children with dyslexia did not show a significantly linear CA trajectory on this task making statistical analysis inappropriate, however a similar amount of delay was evident in the trajectory analysis. The 1 rise task has been the most consistent auditory measure differentiating children with dyslexia and controls in our studies of dyslexia in other languages (Finnish, Hämäläinen et al, 2009 ; Spanish, Goswami et al, 2011 ; Chinese, Wang, Huss, Hämäläinen, & Goswami, 2012 ). A similar 1 rise task based on complex noise rather than a sine wave was also a successful discriminator in a study of dyslexia in Dutch by Poelmans et al, (2011) .…”
Section: Discussionmentioning
confidence: 77%
“…According to the Temporal Sampling Framework (TSF; Goswami, 2011 ), many of the processing deficits observed in dyslexia may be accounted for by inefficient entrainment of brain oscillations to sensory input, which in turn is theorized to affect not only rhythm processing but also phonological processing as well as other aspects of language processing. Studies investigating neural entrainment in individuals with dyslexia support this hypothesis by showing deficits in synchronization to the speech envelope ( Leong & Goswami, 2014 ; Molinaro et al, 2016 ; Power et al, 2016 ) regardless of the language spoken (e.g., English: Goswami et al, 2010 ; English and Hungarian: Surányi et al, 2009 ; Chinese: Wang et al, 2012 ) and atypical neural entrainment to nonspeech stimuli compared to controls ( Cutini et al, 2016 ; Frey et al, 2019 ). Further studies have shown impaired beat synchronization in individuals with dyslexia ( Colling et al, 2017 ; Overy et al, 2003 ; Thomson & Goswami, 2008 ).…”
Section: Atypical Rhythm In Children With Atypical Speech/language Dementioning
confidence: 95%
“…Wang et al (2012) found that in children with DD, accurate discrimination of variation in intensity and rise time was a significant predictor of reading accuracy in Chinese, even if intensity discrimination was not found to be an important source of inter-individual differences in many alphabetic languages (Muneaux et al, 2004; Richardson et al, 2004; Goswami et al, 2010; Hämäläinen et al, 2013). Furthermore, Wang et al (2012) found that duration and frequency discrimination contribute significant unique variance to tasks of onset and rhyme awareness.…”
Section: Introductionmentioning
confidence: 94%